Research on the impact of digitalization on energy companies’ green transition: new insights from China - Ren, Yangjun; Xia, Yuening (Frontiers in Energy Research, 2024)
Digitization has become a core engine for China's energy companies to achieve green transition in a competitive marketplace. Using the panel data of China's A-share listed energy companies, this study explores the impact of digitalization on energy companies' green transition. The finding demonstrates that digitalization can significantly drive energy companies' green transition. This finding remains valid following a series of robustness tests. Moreover, digitalization can indirectly enhance energy companies' green transition by enhancing technological innovation and optimizing operational capacity. Further research demonstrates that the promoting effect of digitalization on green transition in the state-owned companies, growing and mature energy companies and companies in the east are more fully released. This research could assist policymakers and professionals in energy companies with decision-making references to promote green transition.